Peningkatan Hasil Belajar Peserta Didik Menggunakan Model Problem Based Learning pada Elemen Pancasila di Kelas V SDN 10 Bandar Buat - Putri. L, Sabrina Novita; Anita, Yesi; Waldi, Atri; Ahmad, Syafri (Indo-MathEdu Intellectuals Journal, 2025)
This study was motivated by the low level of active involvement of students in Pancasila Education, which has an impact on their understanding of concepts, skills, and attitudes. The purpose of this study was to describe the improvement in student learning outcomes through the application of the Problem-Based Learning (PBL) model in Grade V at SDN 10 Bandar Buat. This research is a Classroom Action Research conducted in two cycles with four stages, namely planning, implementation, observation, and reflection. Data were obtained through observation, tests, and non-tests, with the research subjects consisting of classroom teachers and 25 students. The results showed an improvement in the quality of learning, teacher activities, student activities, and learning outcomes. In terms of attitude, the average score increased from 72.95 in cycle I to 82.88 in cycle II. In terms of knowledge, the average score increased from 76.95 in cycle I to 86.41 in cycle II. Meanwhile, in terms of skills, the average increased from 71.19 in cycle I to 85.32 in cycle II. These findings indicate that the application of the Problem-Based Learning model is effective in increasing student participation and learning outcomes in Pancasila Education in grade V at SDN 10 Bandar Buat